Purification and characterization of cyclodextrin glucanotransferase from alkalophilic Bacillus sp. G1 - Ho, Kek Sian (2005)
A cyclodextrin glucanotransferase (CGTase) was successively purified by ammonium sulphate precipitation, and affinity chromatography on a-CD (epoxy)-Sepharose 6B column. The specific activity of the CGTase was increased approximately 2200-fold, from 8.43 U/mg protein to 18,866 U/mg protein. SDS-PAGE showed that the purified CGTase was homogeneous and the molecular weight of the purified CGTase was about 75 kDa. The molecular weight of the enzyme that was estimated by gel filtration under native condition was 79 kDa. This has indicated that Bacillus sp. G1 CGTase is a monomeric protein. The isoelectric point (pI) of the enzyme was about 8.8. Characterization of the enzyme exhibited optimum pH and temperature of 6.0 and 60 8C, respectively. The enzyme was stable from pH 7.0 to 9.0 and retained its high activity up to 60 8C. However, in the presence of 20 mM Ca2+, the purified CGTase is able to prolong its thermal stability up to 70 8C. CGTase was strongly inhibited by ZnSO4, CuSO4, CoCl2, FeSO4, FeCl3 and EDTA. Km and Vmax for the purified enzyme were 0.15 mg/ml and 60.39 mg bcyclodextrin/( ml min), respectively, with soluble starch as substrate. In cyclodextrin production, tapioca starch was found to be the best substrate used to produce CDs. The enzyme produced g- and b-CD in the ratio of 0.11:0.89 after 24 h incubation at 60 8C, without the presence of any selective agents.